The Burden of Illness of Acute Exacerbation of Asthma - Iqbal, Muhammad Shahid (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: The objective of this study was to determine the direct cost of acute exacerbation of asthma (AEXA) among asthmatic patients. Materials and Methods: A total of 111 asthma patients who were admitted to a public hospital with AEXA included in this study. The costs, including investigation charge, unit costs of treatment per bed, medication charge, food costs, transportation costs, and loss of productivity per asthma episode, were calculated. Data were analyzed using Statistical Package for the Social Sciences (SPSS) ver.23.0. Results: A median medical cost of AEXA under the government perspective was USD 105.00 per episode. Medication cost comprised the majority (52.38%) of the total medical costs and lab investigations. A median medical cost of AEXA under the patient’s perspective was USD 22.50 per episode. Conclusion: AEXA and total days stay in the hospital were directly proportional to the total direct costs.